2021
DOI: 10.1172/jci.insight.147057
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid mobilization from adipose tissue is mediated by CD36 posttranslational modifications and intracellular trafficking

Abstract: The mechanism controlling long-chain fatty acid (LCFA) mobilization from adipose tissue (AT) is not well understood. Here, we investigated how the LCFA transporter CD36 regulates this process. By using tissue-specific knockout mouse models, we show that CD36 in both adipocytes and endothelial cells mediates both LCFA deposition into and release from AT. We demonstrate the role of adipocytic and endothelial CD36 in promoting tumor growth and chemoresistance conferred by AT-derived LCFA. We show that dynamic cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 76 publications
(171 reference statements)
0
33
0
Order By: Relevance
“…The potential explanation for this is that CD36 regulates MMP28 primarily via intracellular mechanisms independent of its function as a FA transporter. Indeed, several studies showed that besides functioning on the membrane as a FA transporter, CD36 may play other roles such as facilitating intracellular traffic of FAs and increasing the rate of intracellular esterification and, thus, regulating cellular signaling and metabolism without catalyzing the translocation of FAs across the plasma membrane [ 54 , 55 , 56 ]. To support the intracellular role of CD36, our published work shows a significant increase in cytosolic CD36 staining in tumor tissues as compared to normal mucosa [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential explanation for this is that CD36 regulates MMP28 primarily via intracellular mechanisms independent of its function as a FA transporter. Indeed, several studies showed that besides functioning on the membrane as a FA transporter, CD36 may play other roles such as facilitating intracellular traffic of FAs and increasing the rate of intracellular esterification and, thus, regulating cellular signaling and metabolism without catalyzing the translocation of FAs across the plasma membrane [ 54 , 55 , 56 ]. To support the intracellular role of CD36, our published work shows a significant increase in cytosolic CD36 staining in tumor tissues as compared to normal mucosa [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VEGF-B is co-expressed with mitochondrial proteins to coordinate FA β-oxidation in adipocytes and reduce the lipid accumulation in adipocytes [ 43 ]. Recently, a low-density lipoprotein receptor-related protein 1 (LRP1) was reported to induce lipogenesis by activating PPARγ signalling in white adipocytes [ 44 , 45 ]. The molecular mechanism of AdECs for controlling lipid catabolism was also demonstrated to involve endothelin-1, which, as an angiogenesis inhibitor, could suppress hormone-sensitive lipase-mediated lipolysis of adipocytes [ 46 , 47 ].…”
Section: Adecs: the Gatekeeper Of Adipocyte Metabolismmentioning
confidence: 99%
“…It facilitates fatty acid (FA) transport into white and brown adipose tissue, heart and skeletal muscle, but the mechanism is not well-understood (12). Recent data also suggest a role in dermal albumin transcytosis, adipocyte FA export, and in tumor growth and metastasis (13)(14)(15)(16). Structurally, CD36 has two transmembrane domains that terminate with very short intracellular domains (17).…”
Section: Introductionmentioning
confidence: 99%